2001
DOI: 10.1562/0031-8655(2001)074<0318:etbitt>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that bcl-2 is the Target of Three Photosensitizers that Induce a Rapid Apoptotic Response¶

Abstract: We originally proposed that the subcellular target for one class of photosensitizing agents was the mitochondrion. This classification was based on effects that occur within minutes of irradiation of photosensitized cells: rapid loss of the mitochondrial membrane potential (delta psi m), release of cytochrome c into the cytosol and activation of caspase-3. These effects were followed by the appearance of an apoptotic morphology within 30-90 min. Fluorescence localization studies on three sensitizers initially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 112 publications
(61 citation statements)
references
References 29 publications
2
59
0
Order By: Relevance
“…This finding is consistent with the conclusion ) that Bax or Bak is needed as an effector of apoptosis, even when antiapoptotic Bcl-2 proteins are neutralised by the overexpression of BH-3 peptide. The requirement that Bax must be activated and migrate to the mitochondria for the release of cytochrome c would predict (a) a delay in the cytochrome c release process after PDT, as we previously observed in mouse lymphoma LY-R cells and in human tumour A431 and MCF-7 cells Lam et al, 2001;Xue et al, 2001b) and (b) temperature dependence of the processes of Bax migration and cytochrome c release (Kessel and Castelli, 2001). In contrast, the prediction is inconsistent with earlier reports of an immediate release of cytochrome c following PDT (Granville et al, 1998;Kessel and Luo, 1998).…”
Section: Discussionmentioning
confidence: 78%
“…This finding is consistent with the conclusion ) that Bax or Bak is needed as an effector of apoptosis, even when antiapoptotic Bcl-2 proteins are neutralised by the overexpression of BH-3 peptide. The requirement that Bax must be activated and migrate to the mitochondria for the release of cytochrome c would predict (a) a delay in the cytochrome c release process after PDT, as we previously observed in mouse lymphoma LY-R cells and in human tumour A431 and MCF-7 cells Lam et al, 2001;Xue et al, 2001b) and (b) temperature dependence of the processes of Bax migration and cytochrome c release (Kessel and Castelli, 2001). In contrast, the prediction is inconsistent with earlier reports of an immediate release of cytochrome c following PDT (Granville et al, 1998;Kessel and Luo, 1998).…”
Section: Discussionmentioning
confidence: 78%
“…Localization and other properties of CPO have been described. 9,18 CPO was dissolved in DMSO to yield a 1mMstock solution. This was stored at 4 °C under nitrogen.…”
Section: Experimental Drugs and Chemicalsmentioning
confidence: 99%
“…In the latter organelle, Pc 4 was also found to bind in the close vicinity of the lipid cardiolipin, a product unique to mitochondria; this may provide a basis for the resulting mitochondrial photodamage [6]. We discovered [7] that three other photosensitizing agents also targeted Bcl-2: the tin etiopurpurin termed SnET2, the porphycene CPO [9-capronyloxy-tetrakis(methoxyethyl) porphycene], and mTHPC (metatetrahydroxyphenyl) chlorin). This report also demonstrated that Bcl-2 photodamage did not result in loss of the mitochondrial membrane potential unless the temperature was raised above 15 °C.…”
Section: Apoptotic Responses To Pdt: the Role Of Bcl-2mentioning
confidence: 99%
“…Our assumption was that more cells would ultimately become apoptotic with time, and that an LD 90 PDT dose would eventually lead to a 90% apoptotic cell population, but this was never clearly established. Another unanswered question was the ability of PDT directed toward ER and/or mitochondria to kill a cell population even when apoptosis was inhibited by caspase inhibitors [7] or where the cell line lacked caspase-3 or Bax [27,28], important elements of the program.…”
Section: Autophagic Responses To Photodamagementioning
confidence: 99%